Evaluation of sixteen children with pseudotumor cerebri - Incecik, Faruk; Hergüner, M Ozlem; Altunbaşak, Sakir (The Turkish Journal of Pediatrics, 2011)
Pseudotumor cerebri (PTC) is a clinical condition characterized by signs and symptoms of increased intracranial pressure, such as headache and papilledema. A total of 16 patients diagnosed with PTC [12 (75%) female; 4 (25%) male] were included in the study. The age of onset of symptoms was 123.4 +/- 34.3 months (range: 60-168 months). Obesity was found in four (25%) of them. Two patients had venous sinus thrombosis, two had corticosteroid withdrawal, and one had posttraumatic PTC. The most common symptom was headache, recorded in 93.8% of the patients. All patients were treated medically. Two patients in our group also required a lumboperitoneal shunt. In conclusion, PTC in children is rare. Both papilledema and sixth nerve palsy resolved rapidly with treatment. However, children can sustain loss of visual field and visual acuity despite treatment.